Excitation of radial collective modes in a quantum dot: Beyond linear response. Issue 5 (12th June 2014) - Gudmundsson, Vidar; Hauksson, Sigtryggur; Johnsen, Arni; Reinisch, Gilbert; Manolescu, Andrei; Besse, Christophe; Dujardin, Guillaume
<x xml:space="preserve">Abstract</x> A non conventional source or receiver of THz and above THz electromagnetic radiation is proposed. Specifically, electron or hole oscillations in DNA dimers (two interacting DNA base‐pairs or monomers) are predicted. The investigation is extended to DNA trimers. Generally, increasing the number of monomers above three, the system becomes more complex and periodicity is lost. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>